On Strengthening the Glass Ceiling of Training for Robotics Competitions: Methods, Issues, and Directions - Dantas, Igor Matias de Lima; Freitas, Marcus Vinícius Lima de; Souza, Larissa Soares de; Alves, Karina M. S.; Silva, Maria Da Guia Torres Da; Goncalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This study presents case studies of workshops de-signed to train teams for participation in robotics competitions, specifically the Brazilian Robotics Olympiad (OBR) and the First Lego League (FLL). The methodologies implemented are detailed, including team selection processes, the introduction of programming tools like Scratch, and the use of simulated competitions. The findings highlight the importance of rigorous planning and the involvement of experienced mentors, which significantly improved students' technical skills, teamwork, and problem-solving abilities. Additionally, key challenges such as resource limitations and motivational factors that impact the effectiveness of educational robotics initiatives are identified. Directions that can motivate the holding of these competitions in schools are pointed out, provided they are combined with methods and techniques that have a strong theoretical basis in educational practice, aiming at the formation of the student as a social being.